2014
DOI: 10.1074/jbc.m114.552638
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Eukaryotic Translation Initiation Factor 4E and Eukaryotic Translation Initiation Factor 4E-binding Protein (4EBP) and Their Upstream Signaling Components Undergo Diurnal Oscillation in the Mouse Hippocampus

Abstract: Background: mRNA translation is crucial for formation of long-term memory. Results: Phosphorylation of eIF4E, 4EBPs, rpS6, Akt, mTOR, and ERK1/2 undergoes diurnal oscillation in mouse hippocampus. Conclusion: Diurnal oscillation in markers of mRNA translation initiation is critical for memory consolidation and persistence. Significance: Circadian oscillation in mRNA translation initiation provides a potential mechanism for persistence of long-term memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…Although rhythmic coordination of transcription and mRNA accumulation has been extensively studied during the last decades, rhythmic translation has been described only recently in mammals. Indeed, it has been shown that the TORC1 pathway is rhythmically activated in mouse liver (12,49), hippocampus (50), and SCN (51), influencing in this way rhythmic ribosome biogenesis (12) or light response and circadian behavior (52,53). Moreover, the circadian clock, in coordination with feeding rhythms, seems to play a modulating role in this activation (12,54,55).…”
Section: Translation Efficiency Is Regulated During the Diurnal Cyclementioning
confidence: 99%
“…Although rhythmic coordination of transcription and mRNA accumulation has been extensively studied during the last decades, rhythmic translation has been described only recently in mammals. Indeed, it has been shown that the TORC1 pathway is rhythmically activated in mouse liver (12,49), hippocampus (50), and SCN (51), influencing in this way rhythmic ribosome biogenesis (12) or light response and circadian behavior (52,53). Moreover, the circadian clock, in coordination with feeding rhythms, seems to play a modulating role in this activation (12,54,55).…”
Section: Translation Efficiency Is Regulated During the Diurnal Cyclementioning
confidence: 99%
“…Phosphorylation and activation of eIF4E-binding protein 1 (4EBP1) and ribosomal protein S6 are also markers for translation initiation. Therefore, the initiation of translation was measured by monitoring p-EIF4E, p-4EBP1 and Page 18 of 41 A c c e p t e d M a n u s c r i p t 18 pS6 30 minutes after training for contextual fear memory (Saraf et al 2014). Context trained mice but not unpaired controls show significant increases in p-EIF4E, p-4EBP1 and pS6 indicating an increase in protein synthesis in area CA1 following training (Fig.4 ).…”
Section: Initiation Of Protein Synthesis Undergoes Diurnal Oscillatiomentioning
confidence: 98%
“…M a n u s c r i p t 22 A c c e p t e d M a n u s c r i p t 25 4hr. Data is shown as mean ± sem, *** p<0.001 ZT4 hr vs. ZT16 hr using student's t-test (Saraf et al 2014). Step-through latency in passive avoidance.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 2 more Smart Citations